If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 18 = 58 Reorder the terms: 18 + 6x = 58 Solving 18 + 6x = 58 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + 6x = 58 + -18 Combine like terms: 18 + -18 = 0 0 + 6x = 58 + -18 6x = 58 + -18 Combine like terms: 58 + -18 = 40 6x = 40 Divide each side by '6'. x = 6.666666667 Simplifying x = 6.666666667
| 6b^2+43b+72=0 | | 6x+53= | | 7(y+4)+y=3(y+3)+7 | | 0=x^2-9x-11 | | cosx+2=2 | | 6x=0.5(x+77) | | 2w^2+14=102 | | 6x=0.5x+77 | | -9(t+7)=18 | | 27x=19x+95000 | | 5x+2.6-2.2x-3= | | 8m+-5.5=10.1 | | 2.4x-0.6= | | 9x-(8x+4)=2x-18 | | 4.603y^10-1.842y^10=-3.651y^10 | | 8q(216q^3)=0 | | 2x(x+3)=-9 | | 2x+20+33x=80+15 | | 2(7x+2)=14x-4 | | 14x=21y | | 6.2x^10+4.5x^10=3.8x^10+7.9x^10 | | 4.8+6.4x= | | 3x+7*8=45 | | x^2+116=0 | | 6(6x+3)=36x-9 | | -3-y=-7 | | 14x-28=15x | | y+4=-10 | | 4x-2x+6xy+21x+-9xy-9= | | 0.14(x-7)+0.04x=0.02x-0.9 | | 8x+4+10x-8=0 | | 1/4x-4=-3-1/3x |